Triple nitrogen-vacancy centre fabrication by C5N4H n ion implantation - Moriyoshi Haruyama; Shinobu Onoda; Taisei Higuchi; Wataru Kada; Atsuya Chiba; Yoshimi Hirano; Tokuyuki Teraji; Ryuji Igarashi; Sora Kawai; Hiroshi Kawarada; Yu Ishii; Ryosuke Fukuda; et al. (Nature Communications, 2019)
There is an extensive literature discussing the potential applications of individual nitrogen vacancy centres but some proposed developments require the use of multiple, coupled defects. Here the authors demonstrate a method to fabricate coupled nitrogen vacancy centre triplets.